Antibiotic Susceptibility Pattern of Mycobacterium tuberculosis - Subba, S; Singh, S; Khagi, AR; Tuladhar, R; Lekhak, B; Khadka, DK; Shrestha, KB (Journal of Nepal Health Research Council, 2009)
Background: The emergence and spread of DR and MDR-TB threat global TB control. The susceptibility patterns of M. tuberculosis isolates against anti-tuberculosis drugs informs an important aspect of TB controls and surveillance and analysis of local rates of TB drug resistance helps in the detection and monitoring of the extent of DR and MDR strains, indicating the quality of TB control in the country. Methods: A cross sectional study was conducted to find out antibiotic susceptibility pattern of Mycobacterium tuberculosis in pulmonary tuberculosis patients at national tuberculosis center. All the samples were stained by auramine fluorochrome method; processed by NaOH Ogawa Method; primary cultured; subcultured in 2% Ogawa media; cultured in drug LJ media and finally results observed and interpreted. Here Drug susceptibility test was done on M. tuberculosis isolate from each patient by Proportion method as standard protocol. Results: Ethambutol (66.10%) was found to be the most effective anti-TB drug according to the susceptibility test followed by RMP (60.33%), SM (59.66%) and INH (41.69%) against M. tuberculosis. Among 45 isolated untreated patients, primary drug resistance was observed in 20%, to two drugs in 17.77%, to three drugs in 11.11%, to four drugs in 6.66% and primary Multi-drug resistant in 22.22%. Among 250 isolated from previous treated patients, acquired resistance to one drug was found in 23.60%, to two drugs in 12.40%, to three drugs in 16.40%, to four drugs in 18.80% an acquired Multi-drug resistant in 37.20%. Among 250 treated 68.40% (n=171) were relapse,18% ( n=45) were chronic, 7.6% (n=19) were follow-up, 3.2% (n=8) were defaulter, and 2.8% (n=7) were treatment failure. MDR-TB was found the highest in chronic cases (64.44%) followed by follow-up case (47.36%), treatment failure cases (42.85%), relapse cases (27.48%) and default cases (12.5%). A statistical analysis reveals significant relationship between prior history of treatment and the development of drug resistance. However, no significant relationship between age and sex with the emergence of drug resistance isolates. Conclusion: MDR-TB was found the highest in chronic cases (64.44%) followed by follow-up case (47.36%), treatment failure cases (42.85%), relapse cases (27.48%) and Default cases (12.5%). Key words: multi drug, relapse, resistant, sensitivity, tuberculosis DOI: 10.3126/jnhrc.v7i1.2277 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 33-41